VD_FINDINFO Décision / 2025 / 767 vom 2. Oktober 2025 - VD Tribunal cantonal (2025)
RISQUE DE COLLUSION, RISQUE DE RÉCIDIVE, DÉTENTION PROVISOIRE | 221 al. 1 let. b CPP (CH), 221 al. 1 let. c CPP (CH), 221 al. 1bis CPP (CH), 237 CPP (CH)